Impaired Contextual Fear Extinction Learning is Associated with Aberrant Regulation of CHD-Type Chromatin Remodeling Factors - Wille, Alexandra; Maurer, Verena; Piatti, Paolo; Whittle, Nigel; Rieder, Dietmar; Singewald, Nicolas; Lusser, Alexandra (Frontiers in Behavioral Neuroscience, 2015)
Successful attenuation of fearful memories is a cognitive process requiring initiation of highly coordinated transcription programs. Chromatin-modulating mechanisms such as DNA methylation and histone modifications, including acetylation, are key regulators of these processes. However, knowledge concerning the role of ATP-dependent chromatin remodeling factors (ChRFs) being required for successful fear extinction is lacking. Underscoring the potential importance of these factors that alter histone-DNA contacts within nucleosomes are recent genome-wide association studies linking several ChRFs to various human cognitive and psychiatric disorders. To better understand the role of ChRFs in the brain, and since to date little is known about ChRF expression in the brain, we performed a comprehensive survey of expression levels of 24 ATP-dependent remodelers across different brain areas, and we identified several distinct high molecular weight complexes by chromatographic methods. We next aimed to gain novel insight into the potential regulation of ChRFs in different brain regions in association with normal and impaired fear extinction learning. To this end, we established the 129S1/SvImJ (S1) laboratory mouse strain as a model for compromised contextual fear extinction learning that can be rescued by dietary zinc restriction. Using this model along with genetically related but fear extinction-competent 129S6/SvEv (S6) mice as controls, we found that impaired fear extinction in S1 was associated with enhanced ventral hippocampal expression of CHD1 and reduced expression of CHD5 that was normalized following successful rescue of impaired fear extinction. Moreover, a select reduction in CHD3 expression was observed in the ventral hippocampus following successful rescue of fear extinction in S1 mice. Taken together, these data provide novel insight into the regulation of specific ChRFs following an impaired cognitive process and its rescue, and they suggest that imbalance of CHD-type remodeler levels, which consequently may lead to changes of transcriptional programs, may be an underlying mechanism involved in impaired fear extinction learning and its therapeutic rescue.